Game-Based Learning for Special Needs: How Modified Board Games Transform Self-Concept in Students with Physical Disabilities - Arifin, Maryam Aria; Suparno, Suparno (Papanda Publisher, 2025)
Students with physical disabilities frequently demonstrate significantly lower self-concept levels compared to typically developing peers, creating barriers to academic achievement and social integration within inclusive educational settings. Board games have emerged as promising educational tools that can simultaneously address cognitive, social, and emotional development needs through structured yet enjoyable interactions. This classroom action research study investigated the effectiveness of modified board game interventions in enhancing self-concept among three students with physical disabilities (ages 11-13) at SLB Negeri Kutai Timur, Indonesia. The intervention employed modified snake-and-ladder games designed to target four self-concept dimensions: self-confidence, self-perception, adaptive capacity, and social interaction. Data collection utilized structured observations and validated self-concept questionnaires administered across three intervention cycles. Statistical analysis employed paired-samples t-tests following normality and homogeneity testing. Significant improvements in self-concept scores were observed from pre-intervention (M = 42.3%, SD = 7.5) to post-intervention (M = 88.7%, SD = 4.5), t(2) = -12.34, p < 0.001, Cohen's d = 3.18. Behavioral observations revealed substantial increases in voluntary verbal participation (15% to 85%), peer interaction initiation (8% to 78%), and positive self-referencing (5% to 82%). All participants achieved the established success criterion of 80% improvement by the final intervention cycle. Modified board games represent effective, accessible interventions for enhancing self-concept among students with physical disabilities. The structured gameplay provides safe environments for success experiences while facilitating natural peer interactions. These findings contribute to inclusive education literature by demonstrating the therapeutic potential of non-digital gaming approaches. Future research should examine larger samples across extended timeframes with randomized controlled designs to establish broader generalizability and long-term intervention effects.